ANALISIS PENGARUH KOMUNIKASI, INFORMASI, EDUKASI (KIE), KUALITAS PELAYANAN, LOKASI DAN HARGA TERHADAP KEPUASAN PELANGGAN SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN DI APOTEK XYZ (UNIB Press, 2025)
This study investigated the effects of Communication, Information, and Education (KIE), service quality, location, and pricing on customer satisfaction and their subsequent influence on customer loyalty at XYZ Pharmacy. Employing a quantitative descriptive methodology through Structural Equation Modeling (SEM), the data from 277 respondents were collected that provided insights via structured questionnaires. The findings reveal that KIE and pricing exert significant direct impacts on customer satisfaction and loyalty, establishing them as critical factors for maintaining competitiveness in the pharmacy industry. In addition, service quality was found to significantly enhance customer satisfaction, although it does not directly translate to loyalty. Strategic location, on the other hand, plays a pivotal role in fostering loyalty but has a less pronounced effect on satisfaction. Customer satisfaction emerges as a crucial mediating variable, underscoring its importance in bridging service attributes and customer loyalty. The study emphasizes the necessity for XYZ Pharmacy to adopt a holistic and customer-centric approach. This includes leveraging competitive pricing, effective communication, and a strategic location to cater to its core customer base, which predominantly comprises productive-age individuals residing locally. Furthermore, the study highlights the value of integrating technological innovations, such as digital health services, and delivering personalized customer engagement as key strategies for differentiation in an increasingly competitive healthcare market. The research also provides practical implications for pharmacy businesses, suggesting that investments in digital platforms and data-driven customer relationship management can significantly enhance customer retention. This underscores the importance of creating long-term value for both the business and its customers, paving the way for sustainable growth and mutual benefits.